HpSlyD inducing CDX2 and VIL1 expression mediated through TCTP protein may contribute to intestinal metaplasia in the stomach - Qiuping Li (Nature Portfolio, 2017)
Abstract Helicobacter pylori infection is the most important risk factor for gastric intestinal metaplasia (IM). Our previous study demonstrated that infection with H. pylori HpslyD-positive strains associated with IM. To further investigate the signalling pathway involved in HpSlyD-induced IM, CDX2 and VIL1 expressions were determined before and after HpSlyD application. TCTP was knocked down by siRNA or overexpressed by plasmid transfection. An HpSlyD binding protein was used to block HpSlyD’s enzymatic activity. The expression of CDX2 and TCTP in gastric diseases was measured by immunohistochemistry. Our results showed HpSlyD induced CDX2 and VIL1 expressions. TCTP protein expression was markedly increased after application of HpSlyD and in an HpSlyD-expressing stable cell line. Downregulation of TCTP protein led to decreased HpSlyD-induced CDX2 and VIL1. Overexpression of TCTP protein improved the expression of CDX2 and VIL1. Co-application of HpSlyD and FK506 led to significant reductions in CDX2, VIL1, and TCTP expression. Immunohistochemistry demonstrated that CDX2 and TCTP expression was higher in HpslyD-positive specimens compared with HpslyD-negative ones. Expression of CDX2 was positively correlated with TCTP in HpslyD-positive cells. Our study is the first to show that HpSlyD induction of CDX2 and VIL1 expression mediated through TCTP may contribute to IM in the stomach.